2010
DOI: 10.1002/jor.21210
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β induces angiogenesis and innervation in human intervertebral disc degeneration

Abstract: Degenerative disorders of the intervertebral discs (IVDs) are generally characterized by enhanced matrix degradation, angiogenesis, innervation, and increased expression of catabolic cytokines. In this study, we investigated the effects of inflammatory cytokines, IL-1␤, and TNF-␣, on the expression of an angiogenic factor, vascular endothelial growth factor (VEGF), and neurotrophic factors, nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), in human IVD degeneration. IL-1␤ and TNF-␣ stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 22 publications
6
145
0
7
Order By: Relevance
“…The young, healthy intervertebral disc is mainly avascular and aneural except for the outer one-third of the AF [56]. As aging occurs, disc matrix proteoglycan, a known inhibitor of vascular ingrowth, decreases and degenerative changes such as microfissures stimulate growth of innervated, vascularized granulation tissue, which propagates along fissures through the outer AF to the inner AF and NP [43,70]. The vascularized granulation tissue permits the migration of macrophages and mast cells into the area as well.…”
Section: If the Disc Is Aneural And Avascular Why Does It Cause So Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The young, healthy intervertebral disc is mainly avascular and aneural except for the outer one-third of the AF [56]. As aging occurs, disc matrix proteoglycan, a known inhibitor of vascular ingrowth, decreases and degenerative changes such as microfissures stimulate growth of innervated, vascularized granulation tissue, which propagates along fissures through the outer AF to the inner AF and NP [43,70]. The vascularized granulation tissue permits the migration of macrophages and mast cells into the area as well.…”
Section: If the Disc Is Aneural And Avascular Why Does It Cause So Mmentioning
confidence: 99%
“…The vascularized granulation tissue permits the migration of macrophages and mast cells into the area as well. Collectively, the granulation tissue and the infiltrating cells express growth factors and proinflammatory cytokines, including fibroblast growth factor, transforming growth factor b1 (TGF-b1), interleukin (IL) 1b, and tumor necrosis factor a (TNF-a) [1,43,70].…”
Section: If the Disc Is Aneural And Avascular Why Does It Cause So Mmentioning
confidence: 99%
“…The inflammatory cytokine interleukin-1b (IL-1b) is a common proinflammatory factor believed to be involved in osteoarthritis and intervertebral disc degeneration [2,3,[22][23][24]. IL-1b is first synthesized as an inactive precursor to pro-IL-1b, which requires cleavage of its aminoterminal region by caspase-1 to change into the secreted active form.…”
Section: Introductionmentioning
confidence: 99%
“…□ S This article contains supplemental cules aggrecan and collagen type II (9 -12). TNF-␣ and IL-1␤ stimulate production of NGF, BDNF, and VEGF, molecules associated with nerve ingrowth and angiogenesis by nucleus pulposus cells (13). Recent work has shown that both TNF-␣ and IL-1␤ promote NF-B signaling in the nucleus pulposus and control expression of syndecan4, a heparan sulfate proteoglycan involved in ADAMTS5/aggrecanase-2 activation (14).…”
mentioning
confidence: 99%